Incidence of respiratory syncytial virus infection in infants and young children referred to the emergency departments for lower respiratory tract diseases in Italy - Medici, M.C.; Arcangeletti, M.C.; Merolla, et al., R. (Acta Biomedica Atenei Parmensis, 2004)
Background: Respiratory Syncytial Virus (RSV) is the leading cause of emergency visits and hospitalization for acute lower respiratory tract infections (LRTI) in infants and young children worldwide. To collect specific epidemiological data on the incidence of RSV infection among infants referred to Emergency Departments (ED) for LRTI in a Mediterranean country, an Italian multicenter epidemiological surveillance program was established. Methods: Eight pediatric centers throughout Italy participated in this study. The study population included 272 children ≤4 years of age, admitted to the ED between October 2000 and April 2001 for respiratory problems that might be possibly related to LRTI. 152 children were <1 year of age, 50 between 1 and 2 years, and 70 >2 years of age. Data regarding medical history and physical examination were recorded for each child, whereas an immunoenzymatic RSV test (TestPack RSV®, Abbott) was performed on nasal and pharyngeal secretions. Results: Out of 272 tested children, 85 were positive for RSV. The peak of the RSV epidemic occurred in February, with an earlier start and end of the RSV season in the northern and central regions, compared to the southern regions. Major risk factors for RSV infection were younger age (p<0.05) and low weight at birth (p<0.05). Among children positive for RSV infection, 55.2% were <1 year of age, 18.3% were between 1 and 2 years, and 25.7% were > 2 years of age. RSV positivity was associated with a higher rate of hospitalization in the whole study population (p<0.01) and especially in the children ≤12 months of age (p<0.01). Clinical evidence of lower respiratory tract involvement, was also more frequently observed in RSV positive than in RSV negative children, both in the whole study population (p<0.01) and in the ≤12 months of age subgroup (p<0.01). Conclusion: These data confirm that the patterns of RSV infection in Italy are similar to those reported for other countries in the northern hemisphere: RSV is associated with a higher risk of hospitalization and clinically evident LRTI involvement than respiratory infections of other etiologies, especially in infants.